The Fluctuations of Leukocytes and Circulating Cytokines in Septic Humanized Mice Vary With Outcome - Skirecki, Tomasz; Drechsler, Susanne; Hoser, Grazyna; Jafarmadar, Mohammad; Siennicka, Katarzyna; Pojda, Zygmunt; Kawiak, Jerzy; Osuchowski, Marcin F. (Frontiers in Immunology, 2019)
Sepsis remains a major challenge in translational research given its heterogeneous pathophysiology and the lack of specific therapeutics. The use of humanized mouse chimeras with transplanted human hematopoietic cells may improve the clinical relevance of pre-clinical studies. However, knowledge of the human immuno-inflammatory response during sepsis in humanized mice is scarce; it is unclear how similar or divergent mouse and human-origin immuno-inflammatory responses in sepsis are. In this study, we evaluated the early outcome-dependent immuno-inflammatory response in humanized mice generated in the NSG strain after cecal ligation and puncture (CLP) sepsis. Mice were observed for 32h post-CLP and were assigned to either predicted-to die (P-DIE) or predicted-to survive (P-SUR) groups for retrospective comparisons. Blood samples were collected at baseline, 6, and 24h, whereas the bone marrow and spleen were collected between 24h and 32h post-CLP. In comparison to P-SUR, P-DIE humanized mice had a 3-fold lower frequency of human splenic monocytes and their CD80 expression was reduced by 1.3-fold; there was no difference in the HLA-DR expression. Similarly, the expression of CD80 on the bone marrow monocytes from P-DIE mice was decreased by 32% (p<0.05). Sepsis induced a generalized up-regulation of both human and murine plasma cytokines (TNFα, IL-6, IL-10, IL-8/KC, MCP-1); it was additionally aggravated in P-DIE vs. P-SUR. Human cytokines were strongly overridden by the murine ones (approx. ratio 1:9) but human TNFα was 7-fold higher than mouse TNFα. Interestingly, transplantation of human cells did not influence murine cytokine response in NSG mice, but humanized NSG mice were more susceptible to sepsis in comparison with NSG mice (79% vs. 33% mortality; p<0.05). In conclusion, our results show that humanized mice reflect selected aspects of human immune responses in sepsis and therefore may be a feasible alternative in preclinical immunotherapy modeling.